Analysis of viral diversity for vaccine target discovery - KHAN, MOHAMMAD ASİF; Khan, Asif M.; Hu, Yongli; Miotto, Olivo; Thevasagayam, Natascha M.; Sukumaran, Rashmi; Raman, Hadia Syahirah Abd; Brusic, Vladimir; Tan, Tin Wee; August, J. Thomas (My University, 2017)
Background: Viral vaccine target discovery requires understanding the diversity of both the virus and the human immune system. The readily available and rapidly growing pool of viral sequence data in the public domain enable the identification and characterization of immune targets relevant to adaptive immunity. A systematic bioinformatics approach is necessary to facilitate the analysis of such large datasets for selection of potential candidate vaccine targets.